Comments on ‘Ileosigmoid Knot’: Case Report - Atamanalp, Sabri Selcuk (Journal of Liaquat University of Medical & Health Sciences, 2021)
Dear Editor, I read with interest the case report paper by Nazir S 2020,1 who reported a young man with ileosigmoid knotting (ISK), who was diagnosed as an obstructive emergency and treated with emergency surgery. Although ISK is a very rare entity worldwide with a few hundred cases reported to date,2 it is endemic in eastern Anatolia, where I practice. I and my colleagues have 80 cases of experience with ISK over a 54-year period from June 1966 to date, which is one of the largest single-center ISK series over the world.3 Here, I would like to discuss some diagnostic and therapeutic details of ISK presented by the authors. Firstly, bowel gangrene, a catastrophic complication of ISK, develops in about two third of the patients with ISK and worsens the prognosis by doubling the mortality rate.4,5 Conversely, melanotic stool, as was presented in the authors’ case, is determined in anamnesis or digital rectal examination of about one fifth of the patients.6,7 Although fever, leukocytosis, abdominal guarding/tenderness, hypotension/shock, somnolence and acidosis suggest bowel gangrene, unfortunately, except for the melanotic stool, none of these indicators are pathognomonic for ISK. Secondly, although abdominal X-ray radiography generally demonstrates a dilated sigmoid colon in addition to multiple small intestinal air-fluid levels in ISK, computed tomography (CT) or magnetic resonance imaging (MRI) are highly diagnostic with 90% of diagnostic accuracy rate by showing enlarged sigmoid colon in addition to the mesenteric whirl sign, the last which is pathognomonic for volvulus.8,9 Following the usage of CT and MRI by 2000s, the diagnostic accuracy rate of ISK clearly increased. When CT or MRI is not used, the correct diagnosis of ISK is still less than 20%, and fortunately, misdiagnosis generally consists of abdominal emergency, which also requires emergency laparotomy, as was reported by the authors.3 Finally, if a stoma is needed in ISK cases with double segment bowel gangrene, the procedure is applied only for one segment, which demonstrates poor bowel conditions including significant edema, borderline ischemia or difference in proximal and distal bowel ends.5 Nevertheless, if possible, I always prefer and advise to perform a colostomy instead of an ileostomy, contrary to the authors’ practice. I congratulate the authors for their report and look forward to their reply.